Organizational Behavior : A Skill-Building Approach - Neck, Christopher P. (SAGE Publications, Inc. (US), 2023)
Organizational Behavior: A Skill-Building Approach, Third Edition examines how individual characteristics, group dynamics, and organizational factors affect performance, motivation, and job satisfaction, providing students with a holistic understanding of OB. Translating the latest research into practical applications and best practices, authors Christopher P. Neck, Jeffery D. Houghton, and Emma Murray unpack how managers can develop their managerial skills to unleash the potential of their employees.